The research of functional state of the systems of providing of motion for footballers on the preparatory stage - Bitko S.M; Mokhun'ko A.D (Kharkov National Pedagogical University, 2010)
The features of neurodynamic reactions are presented on the different stages of playing activity of footballers. In research took part 18 footballers at the age of 18-22. Research was conducted in the first part of day (9-11 hours) on each of the stages. Changeability of neurodynamic indexes is certain in time of the high functional state of organism and after his fatigue. The most informing indexes of neurodynamic reactions of footballers are exposed. The most informing indexes of the state of footballers are offered.